Research progress in inducing immunogenic cell death of tumor cells - Xie, Deqian; Wang, Qifei; Wu, Guangzhen (Frontiers in Immunology, 2022)
Immunogenic cell death (ICD) is a regulated cell death (RCD) pathway. In response to physical and chemical signals, tumor cells activate specific signaling pathways that stimulate stress responses in the endoplasmic reticulum (ER) and expose damage-associated molecular patterns (DAMPs), which promote antitumor immune responses. As a result, the tumor microenvironment is altered, and many tumor cells are killed. The ICD response in tumor cells requires inducers. These inducers can be from different sources and contribute to the development of the ICD either indirectly or directly. The combination of ICD inducers with other tumor treatments further enhances the immune response in tumor cells, and more tumor cells are killed; however, it also produces side effects of varying severity. New induction methods based on nanotechnology improve the antitumor ability and significantly reduces side effects because they can target tumor cells precisely. In this review, we introduce the characteristics and mechanisms of ICD responses in tumor cells and the DAMPs associated with ICD responses, summarize the current methods of inducing ICD response in tumor cells in five distinct categories: chemical sources, physical sources, pathogenic sources, combination therapies, and innovative therapies. At the same time, we introduce the limitations of current ICD inducers and make a summary of the use of ICD responses in clinical trials. Finally, we provide an outlook on the future of ICD inducer development and provide some constructive suggestions.